TINJAUAN SYARIAH TENTANG PENERAPAN AKAD IJARAH AL MUNTAHIYAH BI AL-TAMLIK DI PERUSAHAAN LEASING SYARIAH - Mudzakkir, Muhammad Fakhruddin; Graha, Andi Nu (An-Nisbah: Jurnal Ekonomi Syariah, 2015)
Public need for  their fnancing  of capital  goods  in accordance with  the principles of Islam, encourages businesses and governments  to create the Islamic fnance company. Basic application of  sharia  leasing  transactions between customers through Ijarah Al Muntahiyah bi Al Tamlik contract based on the Fatwa Dewan Syariah Nasional  No. 09/DSN-MUI/IV/2000  about ijarah fnancing and Fatwa Dewan Syariah Nasional No. 27/DSN-MUI/III/2002 about Ijarah  Al  Muntahiyah  bi Al  Tamlik fnancing. Implementation of sharia fnance leasing company to its customers are still not in accordance with the provisions of DSN 27/DSN-MUI/III/2002 and hadith.Keywords : leasing fnance, ijarah al muntahiyah bi al tamlik